Cyclodextrin-based nanostructures. (February 2022) - Narayanan, Ganesh; Shen, Jialong; Matai, Ishita; Sachdev, Abhay; Boy, Ramiz; Tonelli, Alan E.
Abstract: Cyclodextrins (CDs) are a unique class of molecules that are naturally available via degradation of starchy molecules. Their toroidal structure and abundant presence of hydroxyl groups have given scientists exceptional leverage resulting in synthesizing novel molecules for applications ranging from food packaging, controlled release of small molecules, antibacterial coating, agriculture, and air and water filtration. With the advent of nanotechnology, CDs have positioned itself in a variety of forms such as their ability to act as capping/reducing agents for metallic nanoparticles, or form stable nanofibers or nanoparticles or nano micelles, which can be subsequently utilized for sophisticated applications. In this review, we summarize researches on the presence of CDs in various aspects of nanotechnology ranging from nanoparticles, nanorods, nanomicelles, to nanofibers. In addition, through this review, we provide state-of-the-art applications that are being carried out using these nanostructures.